Propuesta de mejora para la gestión del mantenimiento de los sistemas de distribución de energía eléctrica en las Instalaciones de La Refinería de Cartagena S.A.S. bajo la filosofía Lean Manufacturing y sus herramientas TPM (2023)
In the present degree work, an improvement proposal was carried out for the management of the maintenance of the electrical energy distribution systems in the facilities of the Refinería de Cartagena S.A.S. under the Lean Manufacturing philosophy and its TPM tools. For which, first, an analysis of the current situation of the company was carried out using the FODA tool and the study of historical data in which it was detected that the company had an average compliance with program activities of 86% in the Evaluated period. A 5S diagnosis was also applied, which evidenced the importance of its application to maintain safety, cleanliness and order in the company's work areas. Subsequently, the waste that, according to Lean, was associated with inventories, waiting time, censer movements, and transportation, was identified. And, for its elimination, an improvement plan integrated by the activities to be implemented with their respective managers in the stages of requirement, purchase, logistics and transportation and execution of maintenance was proposed.